Kualitas Hadis dalam Kitab Pelajaran Akhlak Karya Adnan Yahya Lubis - Sari Mawarni (TAFSE: Journal of Qur'anic Studies, 2016)
In the daily practice of Islamic teachings, it is found that some hadiths of unknown quality circulate among the general public and are used as references to educational institutions. The Book of Morals by Adnan Yahya Lubis is one of the works that contains traditions without mentioning the chain of transmission, but has been used as a reference in Islamic boarding schools and other educational institutions. Therefore, a study of the quality of the traditions in the book needs to be done academically, so that it can be seen whether the traditions contained in the book are of maqbul or mardud quality. This research is a literature study, data collection is done through takhrij hadith and analyzed through the jarh wa ta'dil science approach. The results showed that the majority of the hadith studied were narrated by Imam Ahmad, Ali, al-Tirmidhi, Ibn Majah, al-Darimi, Imam Bukhari, Imam Muslim, al-Nasa'i, Imam Malik, Abu Dawud. Of the five samples of hadith examined for the quality of the sanad, one quality hadith is authentic from Imam Ahmad's history, one is hasan quality from Tirmidhi's history, two hadiths are of da'if quality from the path of Imam Ahmad and from the path of Ibn Majah, and one is qualified mawdu' from the history of Ali. It can be concluded that the hadiths in the Moral Lesson book are of maqbul quality and some are mardud. Dalam pengamalan ajaran Islam sehari-hari, ditemukan beberapa hadis yang tidak diketahui kualitasnya beredar di kalangan masyarakat umum dan dijadikan rujukan pada lemabag-lembaga pendidikan. Kitab Pelajaran Akhlak karangan Adnan Yahya Lubis adalah salah satu karya yang memuat hadis-hadis tanpa menyebut sanad periwayatannya, akan tetapi telah dijadikan rujukan di pesantren dan lembaga pendidikan lainnya. Oleh karena itu, kajian terhadap kualitas hadis-hadis dalam kitab tersebut perlu dilakukan secara akademis, sehingga dapat dilihat apakah hadis-hadis yang dimuat dalam kitab tersebut berkualitas maqbul atau mardud. Penelitian ini bersifat kajian kepustakaan, pengumpulan data dilakukan melalui takhrij hadis dan dianalisis memalui pendekatan ilmu jarh wa ta’dil. Hasil penelitian menunjukan bahwa mayoritas hadis yang diteliti, diriwayatkan oleh Imam Ahmad, Ali, al-Tirmidhi, Ibnu Majah, al-Darimi, Imam Bukhari, Imam Muslim, al-Nasa’i, Imam Malik, Abu Dawud. Dari lima buah sampel hadis yang diteliti kualitas sanad, satu hadis berkualitas sahih riwayat Imam Ahmad, satu berkualitas hasan riwayat Tirmidhi, dua hadis berkualitas da’if dari jalur Imam Ahmad dan dari jalur Ibnu Majah, dan satu berkualitas mawdu’ dari riwayat al-Ali. Dapat disimpulkan bahwa hadis-hadis dalam kitab Pelajaran Akhlak ada yang berkualitas maqbul dan ada yang mardud.